Effect of Sexual Orientation on Job Satisfaction: Evidence from Greece - Nick Drydakis (Institute for the Study of Labor (IZA), 2014)
This study investigates the differences in four aspects of job satisfaction between gay men/lesbians and heterosexuals. The analysis results suggest that gay men and lesbians are less satisfied with their jobs, by all job satisfaction measures, than heterosexual employees, all other factors being held constant. Gay men and lesbians who have disclosed their sexual orientation at their present job are more satisfied with their jobs than those who have not. In addition, gay men and lesbians who disclosed their sexual orientation at their current workplace longer ago are more satisfied with their jobs than gay men and lesbians who disclosed their sexual orientation more recently. Moreover, adverse mental health symptoms have the same negative impact on employees' job satisfaction regardless of sexual orientation. Furthermore, gay men and lesbians receive lower wages than comparable heterosexual employees. Whilst, the wage gap due to sexual orientation is greater in the group of very dissatisfied men than in the group of very satisfied men, and gay men and lesbians who have disclosed their sexual orientation at their present job receive lower wages than those who have not, but they still have higher levels of job satisfaction. It seems that the effect of disclosure on job satisfaction is the net effect of the connections between disclosure and job satisfaction.
Keywords: J28; C93; J7; J16; J31; J42; J64; J71; 330; sexual orientation; job satisfaction